Research on Mobile Learning in the English Classroom: Pedagogies, Computer developments and Teachers’ Reactions - Barrientos Amador, Maynor (2019)
The aim of this work is to explore the latest research developments related to the integration of mobile learning into the teaching of English as a foreign language. This research is basically organized into four different categories: (1) research on the use of different mobile devices in the English classes including apps and links; (2) the preparation of English teachers including professionals updating and their general reactions toward mobile learning; (3) the engineering of more sophisticated computer solutions for appropriate integrated mobile learning platforms for the teaching and learning of English; and (4) the different pedagogical strategies developed for mobile learning. It is suggested that, the development of appropriate mobile learning strategies should take into account all the results derived from these four levels of research.